Verification of CIRCLE_3D complex to justify the strength of critical equipment of nuclear power station - Тріщ, Роман Михайлович; Гиря, Наталія Петрівна; Пахалович, Микола Євгенович; Кучер, Сергій Олександрович (Technology audit and production reserves, 2016)
The article deals with the development and verification of CIRCLE_3D complex, which is used for calculation of technical parameters (first of all – the strength characteristics) for survey of critical equipment of nuclear power plant, such as mechanical equipment of the first circuit unit. The calculations are necessary to evaluate the technical condition of equipment considering its degradation and aimed at ensuring nuclear and radiation safety in dealing with mechanical equipment life extension of reactor unit of nuclear power plants. A brief description of the purpose and operational conditions of the critical equipment of nuclear power plant, and the algorithm for technical condition assessment using computer codes to determine the predictive value of the residual life are given. Verification of CIRCLE_3D complex is performed to validate the software implementation of computational methods based on the finite element method. The comparison of simulation results by code CIRCLE_3D and standard PNAE G-7-002-86 and the test results of internationally recognized code ANSYS is given. An excellent reproducibility of test results is noted.